(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In this document, we introduce and investigate two interesting subclasses H_g(n,b,λ,α,δ) and H_g(n,b,λ,α,δ;μ) of analytic functions of complex order in the open unit disk U, which are defined by means of the familiar multipliter operator. For functions belonging to the each of these subclasses, we obtain serveral results involving (for example) cofficient bounds. The results presented here would generalize many known results.